Effect of causative genetic variants on atherosclerotic cardiovascular disease in heterozygous familial hypercholesterolemia patients - Matta, Anthony; Rabès, Jean Pierre; Taraszkiewicz, Dorota; Carrié, Didier; Roncalli, Jérôme; Ferrières, Jean (Frontiers in Cardiovascular Medicine, 2023)
Background: Heterozygous familial hypercholesterolemia (HFH) is an autosomal dominant genetic disorder leading to a lifetime exposure to high low-density lipoprotein cholesterol (LDL-c) level and an increased risk of premature atherosclerotic cardiovascular disease (ASCVD). We evaluate the effect of a causative genetic variant to predict ASCVD in HFH patients undergoing treatment.A retrospective cohort was conducted on 289 patients with possible, probable, and definite diagnosis of HFH according to Dutch Lipid Clinic Network score and in whom DNA analyses were performed and mean LDL-c level was above 155mg/dl. The study population was divided into groups based on the presence or not of a causative variant (pathogenic or likely pathogenic). We observed each of the study's participants for the occurrence of ASCVD.Results: A causative variant was detected in 42.2% of study participants and ASCVD has occurred in 21.5% of HFH patients. The incidence of ASCVD (27% vs 17.4%, p=0.048) and the mean of LDL-c under an optimal medical treatment (226±59mg/dl vs 203±37mg/dl, p=0.001) were higher in HFH-causative variant carriers than others. After adjusting on confounders, ASCVD was positively associated with p=0.004] and tends toward a negative association with HDL-c level [OR=0.140; 95% (0.017-1.166), p=0.059]. There is no more association between the detection of a causative variant and the occurrence of ASCVD [OR=1.708; p=0.102]. Kaplan Meier and long rank test showed no significant differences in event free survival analysis between study groups (p=0.523).In this study population under medical care, it seems that the presence of a causative variant did not represent an independent predictor of adverse cardiovascular outcomes in HFH patients, and LDL-c level played the undisputable causal role.